The Effect Of Work Motivation And Work Discipline On Employee Satisfaction At Pt. Bersama Kita Besar - Rifki, Fajar; Utama, Rony Edward (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to test and analyze the influence of Work Motivation and Work Discipline on Employee Job Satisfaction. The independent variables used are Work Motivation and Work Discipline, while the dependent variable is Employee Satisfaction. The data collection method in this study was carried out by distributing questionnaires to 50 respondents of PT. Bersama Kita Bersama. The research method used is a quantitative method that is associative using primary data. These results indicate that Work Motivation has a positive and significant effect on Job Satisfaction with a calculated t value greater than t table 5.288 2.011 In addition, it is known that the sig. value is 0.001 where the sig. value is smaller than 0.05 or 0.001 2.011 and a significant value of 0.001 3.20 and a significant value of 0.001 0.05